AN EMPIRICAL INVESTIGATION OF METHODS, FOR TEACHING DESIGN PATTERNS WITHIN, OBJECT-ORIENTED FRAMEWORKS - HO, SIN BAN; CHAI, IAN; TAN, CHUIE HONG (WORLD SCIENTIFIC PUBL CO PTE LTD, 2007)
Design patterns have become an important part of modern object-oriented design. It is necessary to evaluate and compare the effectiveness of different methods of pedagogical documentation in teaching design patterns. We compared patterns-style documentation with minimalist documentation. Patterns style disagrees with minimalism in that contextual information is not minimal-it usually contains information other than what needs to be done. The discoveries in this empirical study were two fold. First, the MANOVA (multivariate analyses of variance) shows that the effect of patterns-style documentation and minimalism are different. Second, we proposed a prediction model using a regression modeling technique. Considering these results, we formulate some guidelines for effective framework documentation by applying five of the design patterns within the Swing environment as our case study. Different documentation philosophies are better for different goals. For a simple task, use minimalist documentation. For a much more complex problem such involving five of the design patterns, our empirical results suggest using patterns-style documentation.